KAJIAN TERJEMAHAN KALIMAT YANG MEREPRESENTASIKAN TINDAK TUTUR ASERTIF MENJAWAB DALAM DUA VERSI TERJEMAHAN NOVEL PRIDE AND PREJUDICE - Paramita Widya Hapsari; Nababan M.R.; Djatmika Djatmika (PRASASTI: Journal of Linguistics, 2016)
This research is conducted by analyzing answering speech acts in Pride and Prejudice (PAP) novel and its two translation versions, Shira Media and Qanita Publisher. The aims of this research are to describe: (1) observing or non-observing the maxim, (2) the translation techniques used for translating answering speech acts in PAP novel and its two translation versions, (3) the translation quality of answering speech acts in PAP novel and its two translation versions, (4) the impacts of translation techniques toward the quality of answering speech acts in PAP novel.This is a descriptive-qualitative research. The source of data are documents, PAP novel; and informants who assessed the quality of the translations. The data are answering speech acts in PAP novel and the information about translation quality given by the informants. The techniques of data collection are content analysis, questionaire, and Focus Group Discussion (FGD).Result: It is found out that there are observing and non-observing the maxim used in answering speech acts in PAP novel and its two translation versions. In Shira Media Publisher, the translation techniques used are: established equivalence, variation, borrowing, amplification (explicitation), amplification (addition), reduction, modulation, adaptation, transposition, literal, discursive creation, particularization, and generalization. Established equivalence and variation techniques commonly appear in observing and non-observing maxim quantity. These techniques also produce accurate and acceptable translations. Meanwhile, there are 11 translation techniques used in Qanita Publisher are: established equivalence, variation, borrowing, amplification (explicitation), amplification (addition), modulation, reduction, discursive creation, adaptation, transposition, and particularization. Same as the novel Shira Media Publisher, established equivalence and variation techniques also commonly appear in observing and non-observing maxim.The research findings in this research show that established equivalence technique has positive impact to translation quality. Meanwhile, literal and discursive creation are technique that produce less accurate and less acceptable translation. However, the findings also show the majority of translation techniques used are able to create accurate and acceptable translations.Keywords: cooperative principles, translation techniques, translation quality.